Factors influencing cervical cancer screening uptake among women attending Mahalapye district hospital in Botswana-use of the health belief model - Ibekwe, Chidiebere Maquincy (University of Limpopo ( Medunsa Campus ), 2009)
Cervical cancer is the second highest form of cancer among women in Botswana, with breast cancer being the commonest (Ferlay et al, 2002), and is currently the highest cause of cancer deaths in Botswana (Ferlay et al, 2002). Cervical cancer screening using Pap smear provides an appropriate way for early detection and prevention of cervical cancer if appropriately implemented. Cervical cancer screening was introduced in Botswana in 2003 free of charge to all women of age greater than 18 years attending government hospitals. Despite this step by the government to decrease the mortality and morbidity rates resulting from cervical cancer, the uptake of cervical cancer has remained low among women in Botswana (Botswana central statistic report, 2009). Aim of the study; The study was aimed at identifying and describing factors influencing cervical cancer screening uptake among women greater than 18 years attending Mahalapye District Hospital in Botswana using the Health Belief Model. Methodology; This study was a cross sectional survey in which a questionnaire was used to interview 300 participants in order to assess their perceived susceptibility to cervical cancer, their perceived severity of cervical cancer, their perceived benefits of doing cervical cancer screening and their perceived barriers of seeking cervical cancer screening. Descriptive statistics was used to identify and describe factors influencing cervical cancer screening uptake among women attending Mahalapye District Hospital, Botswana using the Health Belief Model construct. Each question in the questionnaire was scored using a 5-point Likert scale ranged from strongly agree (5) to disagree (1). Negatively worded questions had their scales reversed and scores for each construct of the Health Belief Model was added to get an average. Analysis compared women who had ever had „cervical cancer screening‟ with women who had never had „cervical cancer screening‟. Chi-square statistic was used to test for association of selected variables and binary logistic regression was used to measure the associations for the aggregate score of health belief model constructs. Results; Cervical cancer screening rates was 39%. Participants were aware of the perceived severity of cervical cancer (average response 2.58-3.60), perceived benefits of cervical cancer 6 screening (average response 3.10-4.33) and perceived barriers to seeking cervical cancer screening (average response 2.0-3.44) but these were not significantly associated with screening. The highest predictor of cervical cancer screening was perceived susceptibility and those with high perceived susceptibility were 3.2 times more likely to do cervical cancer screening than those with low perceived susceptibility. Main socio-demographic characteristics significantly associated with perceived susceptibility were employment, monthly income and residential area while perceived severity was significantly associated with monthly income and residential area. Conclusions; Perceived susceptibility to cervical cancer was significantly associated with cervical cancer screening. Educational programs geared towards increasing perceived susceptibility to cervical cancer can significantly improve the uptake of cervical cancer screening in Botswana as well as address issues of barriers and misconceptions associated with low uptake of cervical cancer screening.
Thesis (MPH)--University of Limpopo, 2009.
Keywords: Cervical cancer; Cancer